The Effect of Problem Based Learning Model on Learning Motivation and Student Learning Outcomes on Reaction Rate Material in Class XI SMA Pencawan Medan - Adelina Monica Br Sebayang; Elfrida Ginting (Universitas Lampung, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model in increasing student learning motivation and learning outcomes on Reaction Rate material, as well as to determine the existence of a significant correlation between learning motivation and increased student learning outcomes in the PBL learning model. This research was conducted at SMA Pencawan Medan. The samples used were class XI-1 as the experimental class and class XI-2 as the control class. The instruments used in this study were test instruments in the form of multiple choice objective tests to see students' initial abilities obtained through pretests and student learning outcomes obtained through posttests. The results showed that there was an effect of the Problem Based Learning learning model on increasing student motivation and learning outcomes on reaction rate material. This can be seen from the results of the posttest hypothesis test obtained that Sig. (2-tailed) of 0.001 ≤α (0.05). The results of student learning motivation obtained that Sig. (2-tailed) of 0.000 ≤α (0.05). The relationship between motivation and student learning outcomes shows that the correlation is 0.968.